Victoria Falls hotel guest self service system - Mudimu, Esman Tapfuma (Midlands State University, 2019)
The purpose of the study was aimed at technologically bringing change to the current system in order to increase customer satisfaction and will work as a self-assistant to the guest. The system allows the guests to order and send food order instantly to the backend application from mobile device and also proving capability of providing digital receipts back to guest account. In addition, the application will permit the guests to browse and peruse each restaurant menus. This application was designed a solution to the problems which were being faced by the organization stated in chapter one of this documentation. For instance, the restaurant booking was completely done using paperwork and guests would book through phone calls or visit the guest service desk. Thus these problems arose the need for the development of this system. Furthermore, the planning phase provided a comprehensive feasibility study which objects on justifying the progression of the system development. Outcomes from the feasibility study were used as input in the gathering of the necessary information to develop the system. The fundamental objective of this application is to provide mobile services to in-house guests of the Victoria Falls Hotel who may need services in the comfort of their rooms. This is facilitated through making table bookings through their mobile phones and also requesting for room service by means of posting request to the main system. Security is ensured through username and password